Customer Satisfaction through Brand Image, Price, and Service Quality: Kepuasan Pelanggan Melalui Citra Merek, Harga, dan Kualitas Layanan - Firnanda, Rieke Ayu; Prapanca, Detak (Indonesian Journal of Law and Economics Review, 2025)
General Background: The rapid growth of the fashion retail industry in Indonesia reflects the increasing consumer demand for modern, stylish, and high-quality products. Specific Background: Matahari Department Store, as one of Indonesia’s leading fashion retailers, faces challenges in maintaining customer satisfaction due to intense market competition and evolving consumer preferences. Knowledge Gap: Despite the growing competition in retail, limited studies have comprehensively examined the simultaneous role of brand image, price, and service quality in shaping customer satisfaction at local department stores. Aims: This study aims to determine how brand image, price, and service quality contribute to customer satisfaction at Matahari Department Store Sidoarjo. Results: Using a quantitative descriptive method with 96 respondents and SPSS 22 for analysis, the findings reveal that all three variables—brand image, price, and service quality—have a significant and positive relationship with customer satisfaction. Novelty: The research provides empirical evidence on how these factors jointly strengthen customer loyalty in the Indonesian retail fashion context. Implications: The findings encourage retail managers to focus on consistent brand identity, competitive pricing, and service excellence to sustain customer satisfaction. Highlights: Brand image, price, and service quality significantly shape customer satisfaction. Retail loyalty depends on brand trust and perceived service value. Findings guide competitive strategy in Indonesian fashion retail. Keywords: Brand Image, Price, Service Quality, Customer Satisfaction, Retail Fashion